2011
DOI: 10.1093/infdis/jir409
|View full text |Cite
|
Sign up to set email alerts
|

International Spread of an Epidemic Population of Salmonella enterica Serotype Kentucky ST198 Resistant to Ciprofloxacin

Abstract: National Salmonella surveillance systems from France, England and Wales, Denmark, and the United States identified the recent emergence of multidrug-resistant isolates of Salmonella enterica serotype Kentucky displaying high-level resistance to ciprofloxacin. A total of 489 human cases were identified during the period from 2002 (3 cases) to 2008 (174 cases). These isolates belonged to a single clone defined by the multilocus sequence type ST198, the XbaI-pulsed-field gel electrophoresis cluster X1, and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
315
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(334 citation statements)
references
References 33 publications
15
315
2
2
Order By: Relevance
“…These isolates were resistant to ciprofloxacin at ≥ 8 mg/l, reinforcing the usefulness of collecting quantitative data in the EU Monitoring Programme. A single Polish isolate was also resistant to cefotaxime, an important finding as ciprofloxacin and third-generation cephalosporins are important antimicrobials for the treatment of invasive salmonellosis in man (Le Hello et al, 2011;Wasyl and Hoszowski, 2012).…”
Section: Five Mss Reported Results For S Kentucky In Gallus Gallusmentioning
confidence: 99%
See 1 more Smart Citation
“…These isolates were resistant to ciprofloxacin at ≥ 8 mg/l, reinforcing the usefulness of collecting quantitative data in the EU Monitoring Programme. A single Polish isolate was also resistant to cefotaxime, an important finding as ciprofloxacin and third-generation cephalosporins are important antimicrobials for the treatment of invasive salmonellosis in man (Le Hello et al, 2011;Wasyl and Hoszowski, 2012).…”
Section: Five Mss Reported Results For S Kentucky In Gallus Gallusmentioning
confidence: 99%
“…It was found that 89 % of the 72 isolates examined were resistant to both nalidixic acid and ciprofloxacin, with the unusual feature that the ciprofloxacin MIC was high at ≥ 8 mg/l in almost all resistant isolates. The most frequently observed pulsed-field gel electrophoresis (PFGE) pattern exhibited by the Polish S. Kentucky isolates was indistinguishable from that observed in S. Kentucky ST198 by Le Hello et al (2011), who described the international spread of S. Kentucky ST198 resistant to ciprofloxacin in humans.…”
Section: Resistance Levels In S Kentucky From Poultrymentioning
confidence: 97%
“…The emergence of resistant strains of Kentucky in Egypt and their expansion to African countries [28] can explain its predominance in Morocco. Le Hello et al suggested that the north and east of Africa could be the origin of infections by Kentucky in Europe [29].…”
Section: Discussionmentioning
confidence: 99%
“…recent studies, S. Kentucky exhibits the potential to emerge as the most prominent Salmonella serotype in human disease (1,3).Therefore, this particular serovar is potentially an emerging risk for foodborne illness from a public health standpoint.…”
mentioning
confidence: 99%